2018
DOI: 10.1371/journal.pone.0203106
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder opinions on scientific forest management policy implementation in Nepal

Abstract: Despite its widespread recognition as a successful model of participatory forest management, the community forestry program in Nepal is often criticized for its protection-oriented emphasis. Recognizing the need for more active timber management, the government of Nepal recently adopted a scientific forest management (SFM) policy in the lowland tropical region. In this study, strength, weakness, opportunity, and threat analytical hierarchical process criteria were employed to understand stakeholder perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…In particular, implementation of SciFM in community forests has been widely criticized for the dominance of technical forestry officials and for limiting the role of forest user groups (FUGs) in forest management planning and implementation procedures [27][28][29][30]. Likewise, benefit-sharing among stakeholders and transparency of the processes are equally concerning [15,31]. Since one-third of the country's forest area is being managed under community-based forest management regimes [18], any forest management interventions that include these regimes need to satisfy the stakeholders involved.…”
Section: Creating Enabling Environmentmentioning
confidence: 99%
“…In particular, implementation of SciFM in community forests has been widely criticized for the dominance of technical forestry officials and for limiting the role of forest user groups (FUGs) in forest management planning and implementation procedures [27][28][29][30]. Likewise, benefit-sharing among stakeholders and transparency of the processes are equally concerning [15,31]. Since one-third of the country's forest area is being managed under community-based forest management regimes [18], any forest management interventions that include these regimes need to satisfy the stakeholders involved.…”
Section: Creating Enabling Environmentmentioning
confidence: 99%
“…Along the same lines, Khanal and Adhikari [24] find that SciFM intervention has increased the harvesting of forest products from community forests. Similarly, the arguments by many scholars like Bampton and Cammaert [57] and Joshi et al [31] also support that SciFM implementation is timber-focused. Equally, Basnyat et al [23] describe Nepal's SciFM as timber-centric; users obtain a considerable amount of timber, and they invest time to harvest timber from the forest.…”
Section: Timber Harvesting and Distribution: How The Elite Dominate Wmentioning
confidence: 67%
“…Overall, we found that SciFM intervention in community forest has some positive implications, although several limitations have been demonstrated by recent studies; it is accused of having decreased user power and user participation and posing threats of recentralization [31,39,65]. SciFM has focused on timber harvesting and employed technical aspects that could be a burden to forest users [27,38].…”
Section: Timber Harvesting and Distribution: How The Elite Dominate Wmentioning
confidence: 75%
See 1 more Smart Citation
“…After formulating the Scientific Forest Management Guideline 2014, the scientific forestry has taken momentum in the collaborative forest and in mid-hills community forest area including Kaski district [30]. This demands active forest management and is financially attractive [31]. However, the income from the wood is grounded on the annual allowable cut that is prescribed on forest operational plan of CFUGs.…”
Section: Cfug Income and Expenditurementioning
confidence: 99%